CO2 Reduction Characteristics at Pt0.5Ru0.5/C Cathode of H2-CO2 Polymer Electrolyte Fuel Cell - Shofu MATSUDA; Yuta YOSHIDA; Minoru UMEDA (Electrochemistry)
CH4 production by CO2 reduction using a membrane electrode assembly containing a Pt/C electrocatalyst was recently demonstrated. Because this CO2 reduction reaction occurs at approximately its theoretical electrode potential, it is possible to generate electric power as an H2-CO2 fuel cell by the reduction reaction occurring in combination with the H2 oxidation reaction. However, the CH4-generation reaction deactivated in a short time (∼5 min) due to the influence of the CO adsorbed on the Pt surface (COads) as a reaction intermediate. In this study, we investigated the CO2 reduction using a Pt0.5Ru0.5/C electrocatalyst in order to realize a continuous CH4 production. As a result, steady CH4 generation for more than 15 min with a faradaic efficiency of 12.0 % was observed at 0.22 V vs. RHE under a 4 vol% CO2 atmosphere. In other words, an improved continuous CH4 production was achieved by employing a Pt0.5Ru0.5/C electrocatalyst instead of Pt/C, and their faradaic efficiencies were equivalent. This result was obtained because the adsorption energy of COads decreased due to the alloying of Pt and Ru based on the changes in the onset potential of the CH4 production. In addition, power generation as an H2-CO2 polymer electrolyte fuel cell was observed while converting CO2 to CH4.